A7.06 Low-dose IL-2 therapy in refractory sle: Insights from a phase I/IIA clinical trial. (24th February 2016) - Humrich, JY; von Spee-Mayer, C; Siegert, E; Bertolo, M; Abdirama, D; Rose, A; Enghard, P; Radbruch, A; Burmester, GR; Riemekasten, G
Abstract : Interleukin-2 (IL-2) is crucial for the growth and survival of regulatory T cells (Treg), and thus for the control of autoimmunity. In previous studies we have proven the significance of an acquired IL-2 deficiency and related Treg defects in the pathogenesis of systemic lupus erythematosus (SLE). Accordingly, we showed that compensation of IL-2 deficiency by IL-2 therapy corrects associated Treg defects and ameliorates already established disease in lupus-prone mice. 1 Proceeding to a clinical translation of IL-2 therapy for SLE, we recently reported a rapid and robust reduction of disease activity in parallel to a remarkable expansion of the Treg population by low-dose IL-2 therapy in one patient with refractory SLE. 2 In addition, we showed that Treg defects in SLE patients are associated with IL-2 deficiency, and can be selectively corrected in vitro and in vivo with low doses of IL-2. 3 Together, these studies provided the rationales for the clinical implementation an IL-2-based immunotherapy for the treatment of SLE with the aim to restore Treg activity and thus to re-establish endogenous mechanisms of immune tolerance. Here, we present results from the ongoing phase I/IIa clinical trial (PRO-IMMUN) addressing the safety, tolerability, immunological responses and clinical efficacy of a subcutaneous low-dose IL-2 therapy in patients with refractory SLE. References: Humrich JY, et al . Homeostatic imbalance of regulatory and effector T cells due to IL-2 deprivation amplifies murine lupus. Proc Natl Acad Sci USA. 2007;107(1):204–209 Humrich JY, et al . Rapid induction of clinical remission by low-dose interleukin-2 in a patient with refractory SLE. Ann Rheum Dis. 2015. doi: 10.1136/annrheumdis-2014-206506 von Spee-Mayer C, et al . Low-dose interleukin-2 selectively corrects regulatory T cell defects in patients with systemic lupus erythematosus. Ann Rheum Dis. Aug 31 2015. doi: 10.1136/annrheumdis-2015-207776. [Epub ahead of print]